A study on factors that influence the demand for fast food among students in UiTM Malacca City Campus / Syafiqah Suhaini and Akmal Arief Zulkipli - Suhaini, Syafiqah; Zulkipli, Akmal Arief (Faculty of Administrative Science and Policy Studies, 2013)
This research is the study about the demand for fast food among students in UiTM Melaka City Campus. This research is carried out in order to identity the relationship between demand for fast food and the student’s economic, to examine relationship between demand for fast and student’s social, to study relationship between demand for fast food and the fast food’s services. Last but not least, the highest factor that influence the demand for fast food among students in UiTM Melaka City Campus.